Experimental study on condensation of high-pressure steam in a horizontal tube with pool boiling outside. (May 2017) - Nie, Zesen; Bi, Qincheng; Lei, Shiyi; Lv, Haicai; Guo, Yajun
Highlights: New measurement methods of outer wall temperature and heat flux were introduced with good verification results. Pool boiling regimes were obtained as the representation of heat transfer enhancement. Three previous correlations which apply to the annular flow pattern were assessed with the experimental results. A modified correlation was proposed to predict the condensation heat transfer coefficients. Abstract: In order to investigate the heat transfer and resistance performance of high-pressure steam in-tube condensation with pool boiling outside the tube, experiments were conducted on a short horizontal tube with a 25 mm outer diameter and 3 mm wall thickness. The test parameters were in the range of 4–10 MPa pressure, 400–1000 kg/m 2  s mass velocity, and 0.1–0.9 steam quality. New measurement methods of wall temperature and heat flux were introduced. It is found that the outer wall temperature distribution is not uniform in the circumferential direction, and the wall temperature and heat flux increase with pressure, mass velocity, and steam quality. The condensation heat transfer coefficient and frictional pressure drop increase with the mass velocity and steam quality, but decrease with pressure. In addition, the pool boiling regimes were captured by a high-speed camera. The experimental condensation heat transfer coefficients were compared with available existing correlations, and the comparison results were found to be unsatisfactory. Finally, a modified condensation correlation from Akers et al. was proposed for high-pressure steam in-tube condensation with pool boiling outside in smooth horizontal tubes.